Schiff Bases of Tetrahydrocurcumin as Potential Anticancer Agents. Issue 1 (8th January 2019) - Mahal, Ahmed; Wu, Ping; Jiang, Zi‐Hua; Wei, Xiaoyi
Abstract: Tetrahydrocurcumin (THC) is a metabolite of curcumin and a valuable lead structure in medicinal chemistry due to its curcumin‐induced biological effects and its derivatives can be promising antitumor agents. Thirteen Schiff base derivatives of THC (1 ‐13 ) were synthesized by direct condensation of THC with various primary amines in moderate to very good yield (45‐94%) and their structures confirmed by 1 H NMR, 13 C NMR, HR‐ESI‐MS and IR techniques. Furthermore, these compounds were screened for in vitro anticancer activity against three human cancer cell lines including human epithelial lung carcinoma (A549), human epithelial cervical cancer (HeLa) and human breast adenocarcinoma (MCF‐7). Most compounds exhibit moderate to good anticancer activity against all three tested cell lines and are significantly more active than THC. Compound12 bears an N ‐(4‐trifluromethyl)phenylethyl group and is the most active compound with IC50 values ranging from 4.8 to 12.7 μM. The results obtained herein are important for further structure modifications of THC and the exploitation of the therapeutic potential of THC derivatives as anticancer agents. Abstract : A series of 13 Schiff bases were synthesized through structural modification on the tetrahydrocurcumin scaffold. The newly synthesized target compounds evaluated for their in vitro anticancer activity against human epithelial lung carcinoma (A549), human epithelial cervical cancer (HeLa) and human breast adenocarcinoma (MCF‐7). Selectivity towards human breast adenocarcinoma (MCF‐7) over other cancer cells was observed and the most active compound12 exhibited higher potency against all three cancer cell lines.